Experience of Student Entrepreneurs in the Implementation of Businesses Financed with Non-Reimbursable Funds - Dragomir Camelia-Cristina; Zamfirache Alexandra; Foris Tiberiu (Studies in Business and Economics)
This research aims to provide an in-depth understanding of the entrepreneurial experience of students who have received non-reimbursable funding through a project co-funded by the European Union to set up and develop their businesses, and to identify practical solutions to promote student entrepreneurship. To achieve the research objectives, the authors used qualitative research based on the focus group method and the semidirective in-depth individual interview. The results of the research highlighted the factors that encouraged the entrepreneurial intention of the students participating in the study, the advantages they considered they had by participating in the project, as well as the difficulties they faced in the implementation stage of the business. Concrete solutions for promoting entrepreneurial opportunities for students were identified based on the results obtained. The research provides a better understanding of the pathway experienced by student entrepreneurs in the process of business implementation and is useful for current and potential young entrepreneurs who want to access non-reimbursable funds to start a new business, as well as for university management and professors in charge of entrepreneurial training of students who can use the research results to think of new ways to promote entrepreneurial opportunities among students.